Purple corn (Zea mays L.) crop in the Peruvian Highlands: Adaptation and identification of high-yield and high anthocyanin content cultivars - Medina-Hoyos, Alicia (2020)
Purple corn (Zea mays L.) which background is the Kculli race, was originated in the Andean region and is grown in environments as high as 3000 m.a.s.l.; it is unique because of the purple color in the grain and other parts of the plant; the color is due to the presence of anthocyanin such as cianidine-3-glucoside. The objective of this study was to evaluate the grain production and determine the anthocyanin content in the cob and husk of six purple maize cultivars. Anthocyanin content in cob and husk was obtained through the pigment absorbance determination by HPLC (High Performance Liquid Chromatography). Cultivars were planted at 28 environments of Cajamarca during 2016 to 2019. Results indicated that cultivar INIA 601 showed the highest grain yield (2.77 t ha-1) and the highest anthocyanin content in cobs (6.12) and husks (3.18 mg/cianidine-3-glucoside); consequently, using this technology, farmers can develop an agribusiness four times more profitable than growing other types of maize for grain production.